Foliar Uptake of the Potencially Toxic Elements in Garlic Chive Leaves - Seo, Eunseok; Kim, Seonghan; Park, Jiwon; Lim, Heejin; Ha, Nami; Lim, Jun; Lim, Jae Hong; Park, Hyun Jin; Kim, Ki Hean; Lee, Sang Joon (Frontiers in Environmental Science, 2021)
Contamination of vegetables due to the foliar uptake of atmospheric toxic elements could pose severe health risks. However, the uptake mechanisms of potencially toxic elements (PTEs) from the atmosphere and translocation by plant leaves remain unclear. In this study, carboxylic acid-functionalized water-soluble CdSe/ZnS quantum dot nanoparticles (QD NPs) were used as an experimental particle model of PTEs in the edible plant garlic chive (Allium tuberosum). A droplet of QD NP suspension was deposited to simulate the conditions of raindrops containing metal particles falling on a plant leaf. The 3D spatial distribution of QD NPs in plant leaves was measured using three complementary imaging techniques: synchrotron X-ray microcomputed tomography (micro-CT), nano-CT, and two-photon microscopy (TPM). The TPM and micro-CT results revealed that QD NPs deposited on garlic chive leaves penetrated the plant leaves. Nano-CT images showed that QD NPs are absorbed into mesophyll cells and phloem vessels. The results of TEM and TPM imaging demonstrated that QD NPs penetrate through the leaves and translocate in the direction of the stem. The use of these emerging imaging techniques improved the ability to detect and visualize NPs in a plant leaf. These observations also provide mechanistic insights into foliar metal uptake and their translocation and accumulation.